A tale of wandering T-tube: Complete Duodenal Migration and Successful Retrieval - Dahal, Prajwal; Parajuli, Sabina; Dawadi, Kapil (Nepalese Journal of Radiology, 2023)
A 33 years male presented with obstructive jaundice and was diagnosed as chronic cholecystitis with choledochocystolithiasis. The gastroenterology team performed ERCP with sphincterotomy to retrieve stone in common bile duct but failed. Open cholecystectomy with common bile duct exploration was done after few days. T-tube was placed in common bile duct. In the 8th post operative day, tube manipulation was done due to reduced drain output and pain abdomen. We performed T-tube cholangiogram on 12th postoperative day which showed duodenal migration of T tube. The displaced T tube was retrieved using a simple technique.